Conducting a participatory video project with farmers involved in the Fodder Adoption project activities in Mieso Woreda, Ethiopia: Report on a short consultancy - Cullen, Beth (International Livestock Research Institute, 2010)
The aim was to use participatory video as a tool for capturing community views and perceptions on their collaboration with the Fodder Adoption Project over the last 3 years. Fodder Adoption Project of ILRI has been working with farmers and other stakeholders in Mieso woreda since early 2008 to develop fodder resources using a local stakeholder platform for implementation. We wanted to allow our target farmers to give their views on fodder development activities and whether the involvement of a wide group of stakeholders has been a useful approach in terms of accelerating development.